Polyphasic insights into the microbiomes of the Takamatsuzuka Tumulus and Kitora Tumulus - Nishijima, Miyuki; Kiyuna, Tomohiko; Hata-Tomita, Junko; An, Kwang-Deuk; Sano, Chie; Sato, Yoshinori; Sugiyama, Junta; Handa, Yutaka; Nagatsuka, Yuka; Kigawa, Rika; Tazato, Nozomi (Journal of general and applied microbiology, 2017)
Microbial outbreaks and related biodeterioration problems have affected the 1300-year-old multicolor (polychrome) mural paintings of the special historic sites Takamatsuzuka Tumulus (TT) and Kitora Tumulus (KT). Those of TT are designated as a national treasure. The microbiomes of these tumuli, both located in Asuka village, Nara, Japan, are critically reviewed as the central subject of this report. Using culture-dependent methods (conventional isolation and cultivation), we conducted polyphasic studies of the these microbial communities and identified the major microbial colonizers (Fusarium spp., Trichoderma spp., Penicillium spp., dark Acremonium spp., novel Candida yeast spp., Bacillus spp., Ochrobactrum spp., Stenotrophomonas tumulicola, and a few actinobacterial genera) and noteworthy microbial members (Kendrickiella phycomyces, Cephalotrichum verrucisporum (≡Doratomyces verrucisporus), Sagenomella striatispora, Sagenomella griseoviridis, two novel Cladophialophora spp., Burgoa anomala, one novel species Prototheca tumulicola, five novel Gluconacetobacter spp., three novel Bordetella spp., and one novel genus and species Krasilnikoviella muralis) involved in the biodeterioration of mural paintings, plaster walls, and stone chamber interiors. In addition, we generated microbial community data from TT and KT samples using culture-independent methods (molecular biological methods, including PCR-DGGE, clone libraries, and pyrosequence analysis). These data are comprehensively presented, in contrast to those derived from culture-dependent methods. Furthermore, the microbial communities detected using both methods are analytically compared, and, as a result, the complementary roles of these methods and approaches are highlighted. In related contexts, knowledge of similar biodeterioration problems affecting other prehistoric cave paintings, mainly at Lascaux in France and Altamira in Spain, are referred to and commented upon. Based on substrate preferences (or ecological grouping) and mapping (plotting detection sites of isolates), we speculate on the possible origins and invasion routes whereby the major microbial colonizers invaded the TT stone chamber interior. Finally, concluding remarks, lessons, and future perspectives based on our microbiological surveys of these ancient tumuli, and similar treasures outside of Japan, are briefly presented. A list of the microbial taxa that have been identified and fully or briefly described by us as known and novel taxa for TT and KT isolates since 2008 is presented in Supplementary Materials.